Evaluation Results of the First Training Program on Engineering Pedagogy in Chilean Universities - Gormaz-Lobos, Diego; Galarce-Miranda, Claudia; Hortsch, Hanno; Kersten, Steffen; Hinojosa, Jorge; Fuentes, Paul; Rojas, Pablo; Calisto Ulloa, Nancy Cristina; Maldonado Cardenas, Patricia Veronica; Lagos Aguilera, Richard Adolfo; Schaffeld, Guillermo (My University, 2020)
This paper presents the results of a survey focused on the evaluation of an academic training course related to the different pedagogical aspects that influence the training of engineers seeking to improve the quality of teaching and the academic training in the engineering faculties of three Chilean universities (Universidad Autonoma de Chile, Universidad de Magallanes and Universidad de Talca). The training course consists in six modules according to the curricula of the training program "INTERNATIONAL ENGINEERING EDUCATOR ING. PAED.IGIP" of the IGIP center at the TU Dresden, Faculty of Education. The course was offered in blended learning modality with participation of academics from different regions of Chile (Concepcion, Punta Arenas, Santiago, Talca y Temuco). This training program was developed and implemented within the framework of the project "Engineering Didactics at Chilean Universities" (PEDING-Project). The aim of the PEDING-Project was the development and testing of training modules for teaching qualifications of teaching staff in academic Engineering Education based in the IGIP Curriculum offered for the IGIP center at the TU Dresden. The project was led by Prof. Hanno Hortsch (President of IGIP) at the Chair of Didactics of Vocational Learning in the TU Dresden and has been financially supported by the German Academic Exchange Service (DAAD).
Keywords: engineering pedagogy; blended learning; evaluation of peding training course